A Chinese expert consensus on thoracic endovascular aortic repair of type B aortic dissection with a single-branched stent graft for revascularization of the left subclavian artery - Li, Xiaoye; Song, Chao; Zhang, Lei; Yuan, Liangxi; Dai, Xiangchen; Guo, Lianrui; Lu, Qingsheng (Frontiers in Surgery, 2023)
Thoracic endovascular repair (TEVAR) is currently the recommended and most widely used treatment for type B aortic dissection. A major challenge is revascularization of left subclavian artery as to extend landing zone to zone 2 (Ishimaru classification). Different strategies have been used, including branched stent-graft, fenestrated stent-graft, chimney technique, parallel technique, and bypass surgery. Single-branched stent-graft is one of the most promising strategies. Currently, several products have been reported as potential candidate. Castor single-branched stent-graft is the only off-the-shelf product available, which is invented under the cooperation of Chinese corporation and clinicians. In this perspective, experience and data from TEVAR with Castor single-branched stent-graft is summarized by Chinese experienced experts.